The big stick the limits of soft power and the necessity of military force - Cohen, Eliot A. (Basic Books, 2018)
A scholar of international relations outlines compelling arguments in favor of America's enduring relevance and why an active military presence is essential to preserving and enforcing the nation's foreign policies.